Does Covid-19 pandemic influence physical activity level among medical students? An online survey - Abdul Rahman Ramdzan; Chuah, Cheng Yee; Hamshavali Selvaraj; Izian Izani; Md Arman Tanding; Pak, Yue Yuan; Rodrey Raymond; Sabrina Zairul; Wong, Kha Kin; Zulkhairul Naim Ahmad Sidek; Khor, Ban Hock (Universiti Putra Malaysia, 2023)
Introduction: COVID-19 was identified as a global pandemic, and lockdowns have been enforced as part of government policies and public health recommendations. There is not enough data to assess how l lockdowns affect physical activity. Therefore, the purpose of this study is to determine the variations in the level of physical activity among medical students before and during COVID-19 and its associated factors. Methods: From August to October 2020, 225 medical students from Universiti Malaysia Sabah (UMS) participated in this cross-sectional survey. The International Physical Activity Questionnaire (IPAQ) was used to determine participants’ levels of physical activity. The independent t-test was used to determine the relationship between MET score differences in physical activity level and the socio-demographic characteristic and associated factors. The paired t-test was used to compare the MET score of total physical activity before and during COVID-19. Results: Changes in physical activity occurred before and during COVID-19, with the MET level prior to the pandemic being greater. The factors that are discovered to be related with physical activity before and during COVID-19 include M40 household income (p-value = 0.04), no fixed activity schedule (p-value = 0.01), high family demand (p-value = 0.03) and being far away from exercise facilities (p-value = 0.04). Conclusion: The COVID-19 pandemic mitigation strategy has an impact on medical students’ physical activity. Changes in physical activity are influenced by changes in family income and other environmental factors. It may be necessary to take health-promoting actions aimed at inactive people in order to improve wellbeing.